HUBUNGAN ANTARA LOGIKA PROPOSISI DENGAN LOGIKA PREDIKAT (SUATU KAJIAN EPISTEMOLOGIS) - Suyitno, Hardi (MATEMATIKA, 2006)
This paper presentsÂ  epistemological studiesÂ  ofÂ  propositionalÂ  logic andÂ  predicate logic. The topic is a part of the dissertation proposal under title â€œÃ‹pistemology of Mathematical Logic According to Ludwig Wittgensteinâ€.Â Â  Author is a student of the Doctor ProgramÂ  of Gajah Mada University,Â  the majorstudyÂ  isÂ  philosophy. There are someÂ  difference, equality, and relation between propositionalÂ  logic andÂ  predicate logic.Â  Both of them use the same ope-rator, method, and rule ofÂ  inference. There are fiveÂ  operator of logic, thatÂ  areÂ  disjunction, conjunction, negation, implication,Â  and biimplication. The truth value of proposition deter-minated by definition.Â  There are eighteen rules ofÂ  inference, four rules for removing quan-tifiers,Â  and four rules forÂ  introducing quantifiers. There are two methods of validity test, that are direct proof and indirect proof; andÂ  there is one common method for invalidity test , that is Counter Exampel Method. The basic component ofÂ  propositional logic isÂ  simple statement. The basic component of predicate logic is predicate. In the predicate logic beside Counter Exampel Method for invalidity test,Â  there is another method for invalidity test that is Finite Universe Method.Â  The conclusionÂ  of this research isÂ  propositional logicÂ  which a part ofÂ  predicate logic. IfÂ  a form is valid in propositionalÂ  logic, thenÂ  the formÂ  is valid in predicate logics. Thus scope of predicate logic is wider than propositional logic. Â